MANAGEMENT OF STABLE CHRONIC OBSTRUCTIVE PULMONARY DISEASE : A SYSTEMATIC REVIEW - Andreria Hatulely, Chrysman (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Introduction: The goal of drug treatment for chronic obstructive pulmonary disease (COPD) is to relieve symptoms and lower the chance of future problems like flare-ups, disease progression, and death. Because COPD is not all the same, people respond differently to drug treatments. The best way to treat COPD now is with precision medicine, which uses clinical and biomarker data to make treatment decisions that are best for each person. The aim: This article discusses management of stable chronic obstructive pulmonary disease. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search brought up 68 articles, whereas the results of our search on SagePub brought up 32 articles. The results of the search conducted for the last year of 2013 yielded a total 31 articles for PubMed and 15 articles for SagePub. In the end, we compiled a total of 14 papers, 10 of which came from PubMed and four of which came from SagePub. We included four research that met the criteria. Conclusion: COPD treatment has evolved to match clinical characteristics and biomarkers to each patient. Hospitalizations and death have improved in triple combination treatment studies. However, COPD treatments are lacking, such as emphysema-slowing drugs. Despite progress, much remains.